Population-based study of patients with primary Sjögren's syndrome and lymphoma: lymphoma subtypes, clinical characteristics, and gender differences. (3rd May 2020) - Vasaitis, L; Nordmark, G; Theander, E; Backlin, C; Smedby, KE; Askling, J; Rönnblom, L; Sundström, C; Baecklund, E
Abstract : Objective : To examine lymphoma subtypes, clinical characteristics, and gender differences in patients with primary Sjögren's syndrome (pSS) and lymphoma in a population-based setting. Method : Patients with Sjögren's syndrome and lymphoma diagnoses were identified by linkage of the Swedish Patient Register 1964–2007 with the Cancer Register 1990–2007. Clinical data were collected from medical records and lymphoma tissues were re-examined. The lymphoma subtype distribution was compared with the Swedish Lymphoma Register. Results : We identified 105 pSS patients with lymphoma. Diffuse large B-cell lymphoma (DLBCL) (32%) and marginal zone lymphoma [MZL including mucosa-associated lymphoid tissue (MALT) lymphoma] (31%) were the most common lymphoma subtypes. The proportion of DLBCL was not increased compared to the general population reference (32%, p = 1), in contrast to MZL (general population 5%, p < 0.0001). Compared to DLBCL, MALT lymphoma was diagnosed at a younger age (55 vs 67 years, p = 0.0001), and earlier after patient-reported sicca onset (7 vs 18 years, p = 0.0001) and pSS diagnosis (2 vs 9 years, p = 0.0005). Sixteen of the pSS-lymphoma cases were men (15%), twice the proportion in general pSS populations. Compared to women, men had a shorter median time from pSS diagnosis to lymphoma diagnosis (1 vs 8 years, p = 0.0003) and more often had lymphoma in the salivary glands (56% vs 29%, p = 0.04). Conclusion : DLBCL and MZL are common in pSS patients, but only MZL/MALT lymphoma occurs at an increased relative frequency in pSS compared to the general population. The study supports increased awareness of signs of lymphoma in men in the first years after pSS diagnosis.